2011
DOI: 10.1007/s12192-011-0259-5
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-derived bile acids enhance the chaperone activity of α-crystallins

Abstract: Human lens membranes contain the highest cholesterol concentration of any known biological membranes, but it significantly decreases with age. Oxygenation of cholesterol generates numerous forms of oxysterols (bile acids). We previously showed that two forms of the bile acid components-ursodeoxycholic acid (UDCA) and tauroursodeoxycholic acid (TUDCA)-suppressed lens epithelial cell death and alleviated cataract formation in galactosemic rat lenses. We investigated whether these compounds also suppress the ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…In the present study, UDCA treatment mediated modulation to altered tertiary structural changes in a noticeable way. These changes were previously observed and attributed to the power of UDCA to improve the chaperone function of lens crystallins with subsequent reduction of protein aggregations .…”
Section: Discussionsupporting
confidence: 63%
“…In the present study, UDCA treatment mediated modulation to altered tertiary structural changes in a noticeable way. These changes were previously observed and attributed to the power of UDCA to improve the chaperone function of lens crystallins with subsequent reduction of protein aggregations .…”
Section: Discussionsupporting
confidence: 63%
“…On the other hand, other authors have recently demonstrated that TUDCA per se or as a cochaperone of other complexes has a suppressive effect in the thermal aggregation of different proteins in vitro (Berger & Haller ; Song et al . ; Gani et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of millimolar concentrations of TUDCA and UDCA have demonstrated their inhibitory effects on the thermal aggregation of different proteins. 52,53 This effect may have been secondary to the direct stabilization of the protein in question or through direct interaction with other molecular chaperones, enhancing their function. 52,54 However, this chaperone effect is not observed for all proteins; when neurodegenerative diseaserelated proteins like Aβ peptide were tested, TUDCA was found ineffective at preventing aggregation in vitro, 55 although these latter experiments were performed with lower concentrations of TUDCA (micromolar).…”
Section: Lipids and Detergents (Bile Acids)mentioning
confidence: 99%